2022
DOI: 10.1186/s12991-022-00399-x
|View full text |Cite
|
Sign up to set email alerts
|

Ego-resiliency moderates the risk of depression and social anxiety symptoms on suicidal ideation in medical students

Abstract: Background Little is known about the role of protective factors in suicidal ideation among medical students. This study aimed to examine the association between suicidal ideation and protective (self-esteem/ego-resiliency/social support) and risk (depression/social anxiety) factors. Methods Data on sociodemographic factors, depression, social anxiety, self-esteem, ego-resiliency, social support, and current suicidal ideation were collected from 408… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 52 publications
(56 reference statements)
1
11
0
3
Order By: Relevance
“…Unexpectedly, in assonance with the postulations by Johnsons et al ( 2011), the outcomes of the present investigation demonstrated that although scores of the positive sociopsychological factors, i.e., conscientiousness and resilience, negatively correlated with suicidal ideations and attempts, they were not believed to be resilience-bolstering factors as they failed to moderate the link between daily life stress and suicidal ideation or suicidal attempts in a regression analysis. This could appear counterintuitive considering other studies' findings that concluded that conscientiousness (Straus et al, 2019;Lawson et al, 2022) and resilience (Seo et al, 2022) have moderated the effect of psychological problems on suicidal behaviors. This claim could have several explanations, but one is that higher scores of one of the constructs were compensated by the lower scores of another construct, and this observation was supported by the findings of several kinds of research (Johnson et al, 2011;Siegmann et al, 2018).…”
Section: Moderators For Suicidal Attemptsmentioning
confidence: 84%
See 3 more Smart Citations
“…Unexpectedly, in assonance with the postulations by Johnsons et al ( 2011), the outcomes of the present investigation demonstrated that although scores of the positive sociopsychological factors, i.e., conscientiousness and resilience, negatively correlated with suicidal ideations and attempts, they were not believed to be resilience-bolstering factors as they failed to moderate the link between daily life stress and suicidal ideation or suicidal attempts in a regression analysis. This could appear counterintuitive considering other studies' findings that concluded that conscientiousness (Straus et al, 2019;Lawson et al, 2022) and resilience (Seo et al, 2022) have moderated the effect of psychological problems on suicidal behaviors. This claim could have several explanations, but one is that higher scores of one of the constructs were compensated by the lower scores of another construct, and this observation was supported by the findings of several kinds of research (Johnson et al, 2011;Siegmann et al, 2018).…”
Section: Moderators For Suicidal Attemptsmentioning
confidence: 84%
“…Given the in-depth literature review, it was found that the constructs have various abilities and attitudes regarding buffering properties concerning suicidal psychopathologies (Johnson et al, 2011). Literature across Western cultures has concluded that a few of the sociopsychological constructs, despite not having a linear association, had a significant indirect association with psychological outcomes (mainly suicidal behaviors) through interaction with risk factors (hopelessness, depression, anxiety, or stressful life events), and acted as suicidal resilience factors (Siegmann et al, 2018; Brailovskaia et al, 2020; Teismann and Brailovskaia et al, 2020; Seo et al, 2022; Song and Bae, 2022). Hence, previous studies (Johnson et al, 2011; Brailovskaia et al, 2020; Seo et al, 2022) implied that mental well-being, life satisfaction, ego resiliency, and social support have moderated the influence of depression on suicidal ideation among college students and were especially noteworthy for the diminution and prevention of suicidal ideations, whereas self-efficacy, problem-solving abilities, and psychosocial stress resistance were identified to have weaker evidence as a moderator (Johnson et al, 2011).…”
Section: Positive Sociopsychological Constructs and Suicidal Psychopa...mentioning
confidence: 99%
See 2 more Smart Citations
“…Suicidal ideation was a significant risk factor for developing low resilience in our surveyed students. Literature has supported, on many occasions, the buffering ability of resilience against suicidal ideation and attempts, especially among those with depression or anxiety [ 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%